2017
DOI: 10.1590/2317-1545v39n3171313
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in hybrid Brachiaria cv. Mulato II after accelerated aging to overcome dormancy

Abstract: -To evaluate the effect of accelerated aging to overcome dormancy of hybrid Brachiaria cv. Mulato II (U. brizantha x U. decumbens x U. ruziziensis), seeds were collected from two lots with and without scarification, submitted to 42 °C and high humidity (98%) for different periods (0, 24, 48, 72 and 96 h) and then dried at 30 °C to the humidity of 9.1%. The physiological changes were evaluated by tetrazolium, germination, electrical conductivity, respiratory activity and enzymatic evaluation. The exposure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Filho and Usberti (2008) found that the artificially ageing at 40 and 50℃ with 7.6 to 10.8% moisture contents revealed positive effects on seed dormancy releasing in Brachiaria brizantha. Pereira et al (2017) further pointed out that the accelerated ageing up to 48 h can overcome seed dormancy of hybrid Brachiaria cv. Mulato II which is related to increased expression of the α-amylase enzyme, reduction of electrical conductivity values and the changes of antioxidant enzymes, after that, the seed vigor gradually declined from 96 h. Consistently, in the present study the SOD activity was the highest and the MDA content was the lowest in C4, which suggested that the dormancy was partly eliminated by the artificially ageing treatment.…”
Section: R a F T Discussionmentioning
confidence: 99%
“…Filho and Usberti (2008) found that the artificially ageing at 40 and 50℃ with 7.6 to 10.8% moisture contents revealed positive effects on seed dormancy releasing in Brachiaria brizantha. Pereira et al (2017) further pointed out that the accelerated ageing up to 48 h can overcome seed dormancy of hybrid Brachiaria cv. Mulato II which is related to increased expression of the α-amylase enzyme, reduction of electrical conductivity values and the changes of antioxidant enzymes, after that, the seed vigor gradually declined from 96 h. Consistently, in the present study the SOD activity was the highest and the MDA content was the lowest in C4, which suggested that the dormancy was partly eliminated by the artificially ageing treatment.…”
Section: R a F T Discussionmentioning
confidence: 99%
“…Mulato II; a tetraploid hybrid, that the result of three generations of crosses and selection (Teixeira et al, 2018). This species, compared to the Marandu forage, has been identified as a plant that stands out for its productivity, adaptability and ability to tolerate diseases and pests that attack other species of the genus Brachiaria (Ramos and Vital, 2016;Pereira et al, 2017). Thus, it is important to study the response of this plant to nitrogen fertilization in periods of prolonged drought, when compared to the most used species of the genus Brachiaria (Teixeira, 2016).…”
Section: Introductionmentioning
confidence: 99%